Topographical guidance of 3D tumor cell migration at an interface of collagen densities - Bordeleau, Francois (2013)
During cancer progression, metastatic cells leave the primary tumor and invade into the fibrous extracellular matrix (ECM) within the surrounding stroma. This ECM network is highly heterogeneous, and interest in understanding how this network can affect cell behavior has increased in the past several decades. However, replicating this heterogeneity has proven challenging. Here, we designed and utilized a method to create a well-defined interface between two distinct regions of High and Low density collagen gels to mimic the heterogeneities in density found in the tumor stroma. We show that cells will invade preferentially from the High-density side into the Low-density side. We also demonstrate that the net cell migration is a function of the density of the collagen in which the cells are embedded, and the difference in density between the two regions has minimal effect on cell net displacement and distance travelled. Our data further indicate that a Low-to-High density interface promotes directional migration and induces formation of focal adhesion on the interface surface. Together, the current results demonstrate how ECM heterogeneities, in the form of interfacial boundaries, can affect cell migration.